Stress And Aeroelastic Analyses Of Ultralight Aircraft Wing - Kabbarah, Hussam Fatthi A (Universiti Sains Malaysia, 2021)
This paper attempts to study a methodology stress analysis of an ultralight-aircraft’s wing structure imperiled to certain stress loads throughout the research. The analysis will cover static and flutter analysis of the wing’s structure. For static, it is more into lift distributions and the resultant stresses in a 3-dimensional axis. As a first step, the wing was modeled using SolidWorks 2020. The structural components of the wings will consist of primary and secondary spar-webs and cross-sectional ribs attached using SolidWorks 2020 Assembly. NACA 2412 is chosen as the baseline airfoil for wings. The spar-caps were used in the first model, but due to the academic edition of SolidWorks 2020, the number of elements was limited for any additional components. The wing spars and the skin covering are made of Aluminum Alloy, 7075-T6, to reduce the weight of the structure. The first section will investigate the static structural behavior of the wing to give the overall shear, bending, and torsional stresses. A V-n diagram will be established for each wing structure based on the design and flight specifications using MATLAB 2019 edition. The Corresponding Von-Mises tension and comparable elastic strain are obtained to study the mechanical behavior of the wings. Furthermore, the flutter analysis of the structure will cover the calculations of flutter speed from a modal investigation using SOLIDWORKS 2020 software. Also, the modal shape of each mode and its frequency are obtained to analyze the dynamic behavior of the wings. The outcomes from the static and dynamics structure analysis of the ultralight aircraft wings aid engineers to reduce excitation on the natural occurrences and avoid wings from flutter at higher speeds. Given the results obtained in this paper, the analysis showed safe design following FARs (Federal Aviation Regulations) which no permanent deformation and no global buckling will occur at maximum load as well as the factor of safety of 1.5 against ultimate strength was obtained. In conclusion, the sequence of analyzing the wing’s structure never ends and there is room for future improvements for accurate stress analysis and high-grade information.